2020
DOI: 10.3389/fphys.2020.00961
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Connexins 40 and 45 Reduces Local and Conducted Vasoconstrictor Responses in the Murine Afferent Arterioles

Abstract: The juxtaglomerular apparatus (JGA) is an essential structure in the regulation of renal function. The JGA embodies two major functions: tubuloglomerular feedback (TGF) and renin secretion. TGF is one of the mechanisms mediating renal autoregulation. It is initiated by an increase in tubular NaCl concentration at the macula densa cells. This induces a local afferent arteriolar vasoconstriction and a conducted response that can be measured several 100 μm upstream from the juxtaglomerular segment. This spread of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
(97 reference statements)
0
4
0
2
Order By: Relevance
“…[43][44][45][46][47][48] Studies with Cx40-knockout mice have shown the dominant role of Cx40 in the kidney [49][50][51] and systemically. 6,[52][53][54] VSMCs show prominent expression of Cx45 36,55,56 and variable expression of Cx43, mostly in cultured VSMCs. 35 Radial communication from ECs to VSMCs occurs via myoendothelial gap junctions (MEGJs) (Figure 2).…”
Section: Connexinsmentioning
confidence: 99%
“…[43][44][45][46][47][48] Studies with Cx40-knockout mice have shown the dominant role of Cx40 in the kidney [49][50][51] and systemically. 6,[52][53][54] VSMCs show prominent expression of Cx45 36,55,56 and variable expression of Cx43, mostly in cultured VSMCs. 35 Radial communication from ECs to VSMCs occurs via myoendothelial gap junctions (MEGJs) (Figure 2).…”
Section: Connexinsmentioning
confidence: 99%
“…Cx37, Cx40, and Cx43 are expressed in endothelial cells (ECs) and smooth muscle cells (SMCs) [12,66,68,75,[78][79][80]. Cx45 has been observed in the SMCs of cerebral vessels [81][82][83][84]. The goal of the cited studies [12,66,68,73,[75][76][77][78][79][80][81][82][83][84] was to evaluate the role of gap junction channels in microcirculation homeostasis.…”
Section: Connexin Expression In Arteriolesmentioning
confidence: 99%
“…Cx45 has been observed in the SMCs of cerebral vessels [81][82][83][84]. The goal of the cited studies [12,66,68,73,[75][76][77][78][79][80][81][82][83][84] was to evaluate the role of gap junction channels in microcirculation homeostasis. However, the direct contribution of Cxs hemichannels to the regulation of the vasomotor tone was not evaluated and is incompletely understood.…”
Section: Connexin Expression In Arteriolesmentioning
confidence: 99%
See 1 more Smart Citation
“…В сосудах Cx 45 ассоциирован с мРНК α-SMA (α-Smooth muscle actin), а в клубочках -с мРНК PDGFRβ (Platelet-derived growth factor receptor β). Кроме того, имеются данные об экспрессии мРНК Cx 45 интерстициальными фибробластическими клетками [18]. Сведения об экспрессии Сх 45 ренин-секретирующими клетками противоречивы.…”
unclassified